Perancangan Aplikasi Pelayanan dan Konsultasi Hukum Berbasis Web pada Kantor Law Firm Duma & Co - Steven Martinus Pedro Pasaribu; Samuel Ramos; Hany Maria Valentine (Eksplorasi Teknologi Enterprise & Sistem Informasi (EKSTENSI), 2023)
Law Firm Duma & Co is a professional legal consultant with high competence and integrity. The work unit for services and legal consultations is obliged to prepare a strategic plan that contains vision, mission, goals, strategies, policies, services, and is indicative in nature. The problem that occurs in the Duma Law Firm Office is that there is no information service regarding legal services that can be accessed by customers online and the customer must come to the Duma Law Firm Office to conduct a consultation. This process is very time consuming and consulting activities are not well documented due to the absence of complete reports during monitoring or evaluation. With these problems, there is an alternative that can help solve these problems by implementing a reliable computerized system. It is hoped that information can be obtained quickly, precisely and more efficiently and effectively. The design method used in this research is the Unifield Modeling Language (UML) method. While making applications in this study using the PHP programming language while the database uses MySQL.